MODEL PEMBELAJARAN NILAI DAN KARAKTER BERBASIS NILAI-NILAI KEHIDUPAN DI SEKOLAH DASAR - Sa'dun Akbar (Universitas Negeri Malang, 2016)
Value-based Model for the Teaching and Learning of Characters in Primary Schools. This is a descriptive study on the teaching and learning process and problems in the teaching and learning of characters and values in primary schools across East Java. On the basis of the study, the article presents a draft of a (proposed) model for the teaching and learning of values in primary schools. The study was conducted in 13 municipalities/regencies in East Java. The data were collected through questionnaires and interviews. The results indicate that primary schools in East Java have carried out integrated, yet not systemic, teaching and learning of characters and values. One of the salient problems is that life values have not been comprehensively accommodated in the visions, missions, and objectives of the schools, as well as regulations in the schools. The draft of the proposed model takes the form of reformulating schools' visions and their implications for the physical and social arrangements of the schools.   Model Pembelajaran Nilai dan Karakter Berbasis Nilai-nilai Kehidupan di Sekolah Dasar. Penelitian ini bertujuan untuk mendeskripsikan penyelenggaraan dan masalah-masalah pembelajaran nilai dan karakter yang terjadi di SD Jawa Timur, serta menghasilkan draf awal model pendidikan nilai-nilai kehidupan di SD. Penelitian deskriptif ini dilakukan pada 13 kota/kabupaten di Jawa Timur. Data dikumpulkan dengan angket dan observasi, serta dianalisis secara deskriptif. Hasilnya adalah SD di Jawa Timur sudah menjalankan pendidikan nilai dan karakter secara terintegrasi, namun penyelenggaraannya belum dilakukan secara sistemik. Masalah yang dihadapi antara lain nilai-nilai kehidupan belum seluruhnya terakomodasi dalam visi, misi, tujuan, dan berbagai tata tertib yang berlaku di sekolah. Draf awal model pendidikannya berupa reformulasi visi sekolah dan implikasinya terhadap program penataan fisik dan sosial.